Outcome of Prenatally Diagnosed Posterior Urethral Valve Patients - Experience from a Low Income Country (Bangladesh Journal of Endosurgery, 2014)
Purpose: To evaluate the outcome of prenatally diagnosed posterior urethral valve  (PUV) patients in our setup where fetal interventions are not available.Methods: This prospective study included 24 PUV patients (July 2007 to December 2012), who  were diagnosed prenatally but had no prenatal interventions and delivered in our center.  Within 24 hours after birth, all of them had urinary ultrasonography (USG). Voiding  cystourethrography (VCUG) and renogram were done in the second week and  cystoscopy with valve ablation during the same admission period. Patients were  followed up regularly after cystoscopic fulguration. Clinical features, treatment, and  outcomes were analyzed.Results: Predominant clinical features were renal failure  and urinary ascites. Eleven patients (45.8%) had bilateral vesicoureteric reflux  (VUR) of different grades. Eight patients (33.3%) had decreased renal cortical  thickness (